Internalizing Behavior of Sociometrically Neglected Students in Inclusive Primary Classrooms – A Methodological Issue? - Kulawiak, Pawel R.; Urton, Karolina; Krull, Johanna; Hennemann, Thomas; Wilbert, Jürgen (Frontiers in Education, 2020)
Internalizing problems in children belong to the category of special educational needs called emotional and behavioural difficulties. Recent decades have witnessed a critical discussion about whether children and adolescents experiencing internalizing problems are at risk of being sociometrically neglected (neither liked nor disliked by their peers). Previous studies have shown evidence both for and against the association between internalizing problems and neglected sociometric status. These contradictory results may be due to the following methodological aspects: (1) shortcomings of sociometric status classification methods (arbitrariness of the sociometric classification rules) and (2) different operationalizations of internalizing problems (broadband and narrowband dimensions of behaviour). The aim of the present study is to investigate empirically whether and to what extent these methodological aspects lead to contradictory results on the internalizing behaviour of neglected students. This question is investigated using a sample of students (N = 2334) in German inclusive primary schools. The systematic investigation presented here provides initial indications that the various methodological approaches can lead to conflicting results. The contradictory results are not only due to the application of different sociometric classification methods, but also to different operationalizations of internalizing behaviour (narrowband and broadband scales). Earlier contradictory evidence on the internalizing behaviour of neglected students must therefore be seen in a different light: the reasons for previously conflicting results may actually be methodological. Based on the results, conclusions are drawn as to how methodological aspects can be given more consideration in sociometric research on internalizing behaviour.